14 COMPARATIVE EFFECTS OF RAPID BOLUS ADMINISTRATION OF AQUEOUS AMIODARONE VERSUS 10-MINUTE CORDARONE IV INFUSION ON MEAN ARTERIAL BLOOD PRESSURE IN CONSCIOUS DOGS. (1st March 2005) - Somberg, J. C.; Cvetanovic, I.; Ranade, V.; Molnar, J.
Abstract : Introduction: Cordarone IV is an effective antiarrhythmic agent; however, a high incidence of drug related hypotension was reported in clinical trials. The hypotension was not dose related, but related to the rate of infusion. As a result, labeling calls the standard formulation (including generics) to be administered over 10 minutes. The standard formulation contains polysorbate 80 and benzyl alcohol and each causes hypotension. A new aqueous formulation of amiodarone (AA) does not contain these solubilizing agents and therefore may cause less hypotension. This hypothesis was tested in conscious dogs. Methods: Six mature beagle dogs were surgically instrumented with a telemetric device for monitoring of heart rate and blood pressure. The study was run on 5 separate days. On the first 2 days, a 10-minute IV infusion or a bolus of 5% dextrose in water (D5W) was administered (placebo). Over the following 3 days, the dogs received (in randomized order, one per day) a 10-minute infusion of 2.5 mg/kg of Cordarone® IV (C) and bolus administrations of 2.5 mg/kg and 5.0 mg/kg of AA injected over 2 to 5 seconds. The dogs were monitored for 2 hours after dosing (1-min intervals). Results: Bolus administration of AA at either 2.5 mg/kg or 5.0 mg/kg produced no statistically significant changes in the mean arterial blood pressure (MABP) relative to D5W bolus (p>0.25, ANOVA). In contrast, 10-minute infusion of 2.5 mg/kg C produced statistically significant decreases in MABP relative to D5W infusion that lasted for at least 2 hours (p<0.001). The decrease in MABP became statistically significant at 3 min. post dosing (91 vs. 105 mm Hg, p<0.05) with a further drop in MABP to 62 mm Hg (p<0.001) at 10 min post dose. The MABP remained significantly lower until the end of the study (80 vs. 98 mm Hg, p<0.05). Compared to AA boluses, MABP was significantly lower following C infusion. Conclusion: Aqueous amiodarone did not cause hypotension when administered as a rapid bolus. In contrast, 10 minute infusion of the standard preparation, Cordarone IV resulted in a sustained and significant hypotension. The hemodynamic profile of the aqueous formulation was significantly better than C, permitting a more rapid administration.